2016
DOI: 10.1021/acs.jmedchem.5b00911
|View full text |Cite
|
Sign up to set email alerts
|

Conopeptide-Derived κ-Opioid Agonists (Conorphins): Potent, Selective, and Metabolic Stable Dynorphin A Mimetics with Antinociceptive Properties

Abstract: Opioid receptor screening of a conopeptide library led to a novel selective κ-opioid agonist peptide (conorphin T). Intensive medicinal chemistry, guided by potency, selectivity, and stability assays generated a pharmacophore model supporting rational design of highly potent and selective κ-opioid receptor (KOR) agonists (conorphins) with exceptional plasma stability. Conorphins are defined by a hydrophobic benzoprolyl moiety, a double arginine sequence, a spacer amino acid followed by a hydrophobic residue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 87 publications
1
30
0
Order By: Relevance
“…Clinical translation of biased agonism is of critical importance, and studies in recombinant cells should be followed up by experiments in target cells or isolated tissues with direct therapeutic relevance. As described above, the μ‐receptor agonist TRV130 (DeWire et al, ) and the κ‐receptor agonist triazole 1.1 (Brust et al, ) display consistent patterns of bias in HEK293 or CHO‐K1 cells expressing receptors recombinantly compared to native cells or whole animal experiments. In other cases, however, bias or overall pharmacology may differ markedly depending on the experimental system.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Clinical translation of biased agonism is of critical importance, and studies in recombinant cells should be followed up by experiments in target cells or isolated tissues with direct therapeutic relevance. As described above, the μ‐receptor agonist TRV130 (DeWire et al, ) and the κ‐receptor agonist triazole 1.1 (Brust et al, ) display consistent patterns of bias in HEK293 or CHO‐K1 cells expressing receptors recombinantly compared to native cells or whole animal experiments. In other cases, however, bias or overall pharmacology may differ markedly depending on the experimental system.…”
Section: Discussionmentioning
confidence: 75%
“…Recent Phase 3 clinical trials have demonstrated effective post‐operative analgesia following oliceridine treatment, with diminished nausea and vomiting compared to morphine. Another example is the development of biased agonists at the κ‐opioid receptor to treat pain and chronic itch, but lacking the adverse effects of dysphoria and sedation (Brust et al, ). The κ‐receptor agonist triazole 1.1 displayed bias towards beneficial Gαi/o signalling over detrimental β‐arrestin mediated pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated dynorphin A has previously been implicated in the development and maintenance of neuropathic pain, since intrathecal administration of antidynorphin A serum ameliorated pain in an animal model [41]. However, several studies showed that exogenous agents could induce the production of dynorphin A by microglia or neurons leading to an analgesic effect in CCIinduced model [42][43][44]. Further investigating indicated that the analgesic effect by dynorphin A failed to administrate specific anti-dynorphin A antibody or selective κ-opioid receptor antagonist GNTI.…”
Section: Discussionmentioning
confidence: 99%
“…691 Screening of a library of synthetic conotoxin variants has identied a peptide that upon further structure-activity relationship tuning, led to analogues that were potent and selective agonists of the k-opioid receptor. 692 Large quantities of the nAChR antagonist, a-conotoxin LvIA, have been prepared via an E. coli recombinant expression system. 693 Some carnivorous cone snails, including wormhunting snails of the subgenus Rhizoconus, have evolved two distinct venomsone set of peptides for defence, and another set for predation.…”
Section: Molluscsmentioning
confidence: 99%